An Examination of the Determinants of The Mode of Transport to Primary Health Facilities in A Developing Region - Olayinka Otun; Adeolu Dina; Adeola Bamigboye (Indonesian Journal of Geography, 2014)
Access to primary health facilities is a key determinant of the overall well being of the population in an area.   In rural regions were distances to public facilities are usually longer compared to urban areas, it is not clear if people are still willing to walk to use these facilities. It is pertinent therefore to clarify such uncertainty since walking distance is a standard measure used to plan such public facilities particularly in rural regions. The objective  of this study therefore is to provide a framework to determine the factors that will influence a health care service seeker in a developing region to walk or use other means of transport to a primary health facility.  The case study for this research is Ijebu North Local Government Area of Ogun state made up of eleven urban and rural wards. One hundred and fifty households were selected at random for interview. Logit regression was used to describe how some predictor variables were used to explain the likelihood of a particular household walking to a primary health facility. The predicting model  in this study was able to classify 80.0% of the cases correctly.   This simply shows that the predictors (independent variables) contribute to the predicting power of the logistic regression model.   The  pseudo R-squares of Cox and Snell’s R-square and Nagelkerke’s R also show that our logistic model is relevant to predicting whether a household will walk or use a vehicle while attending a health facility.   In our study, we noted that settlement status (p=0.00)  and transport cost to health facility (p=0.00) contributed significantly to the prediction.  This study also reveals that the odds for household members in an urban area to walk to the health facility often used  is 88.1%  lower than the odds for a household in a rural area.   It was revealed that households that are poor are 49% times more likely to walk to the health facility they frequently used. The knowledge of the factors that will determine whether health care service seekers in a developing region will want to walk or not will assist government in the planning and provision of health facilities.